Entre telas: mercado e tecnologia digital na (re)construção do dispositivo pornográfico no Brasil - Santos, Dionys Melo dos (2024)
The main objective of the text on screen is to analyze the current stage of the Brazilian porn industry. More specifically, the following work intends to analyze the impacts of “new” digital technologies, especially smartphones and content sharing platforms, on the national porn ecosystem. In recent years, the porn industry's production chain has been undergoing intense transformations, mainly with regard to the emergence of independent producers who sell their content through applications. “New” bodies and desires, new consumption. Inclusion and diversity are fundamental processes for contemporary capitalism, at least in discourse, and in the pornographic field it would be no different. Starting from empirical research, carried out with national porn producers, through interviews and participation in events aimed at the adult entertainment market, such as business fairs, workshops and parties, this research finds a key point in the concept of “sexual wellness” in a process that aims to increase engagement and encourage the destigmatization of the field.